Miłość ojczyzny w perspektywie chrześcijańskiego powołania do świętości - Adamczyk, Dariusz (Studia Pastoralne, 2009)
A Christian expects a full realization of God’s Kingdom. Heaven is his true homeland. However, he lives an earthly life. The Christian vocation is to promote God’s Kingdom on Earth. In considering the Christian vocation to holiness, Christian love for one’s homeland becomes the dictate of one’s conscience. It is connected with a feeling of duty and responsibility for the homeland. Patriotism isn’t only a human value. Its origin is love of God. Love of one’s homeland is even mentioned in Jesus’ teaching. True patriotism derives from the keeping of the commandment of love. Such behavior guarantees social justice and lasting peace between all people. This rule considers especially those who form a nation. Belonging to a nation obliges people to undertake moral responsibility of acting for the benefit of their homeland. One’s concern for the nation should not be limited to knowledge of the past and of traditions. It’s about one’s personal contribution to the act of creating the present reality in the spirit of the gospels.